Kode Etik Guru Pendidikan Agama Kristen sebagai Landasan Profesionalisme dan Spiritualitas dalam Pendidikan - dorlannaibaho; Mawarni Hutagalung (JOURNAL SAINS STUDENT RESEARCH, 2025)
The code of ethics for Christian Religious Education teachers has an important role as a basis for professionalism and spirituality in the world of education. This research aims to analyze how the code of ethics supports teachers in carrying out their duties professionally and based on the values ​​of the Christian faith. The method used is a literature review to explore theories and practices that are relevant to the development of teacher professionalism and spiritual integrity. The research results show that the code of ethics not only functions as a moral and ethical guideline, but also as a tool for building character, improving the quality of learning, and creating an educational environment that supports the development of spiritual values. By integrating a code of ethics into educational practice, teachers can be role models for students while maintaining commitment to their professional calling and faith.